2016
DOI: 10.7466/jkhma.2016.34.4.139
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Stimulus-Organism-Response Model on Consumer's Continued Intention to Use Mobile Payment Services : Multiple Mediation Model

Abstract: This study uses S-O-R framework to examine the relationships among consumers' perception of economic benefits, usefulness, privacy risks, switching cost, and emotions and continued intention usage. Results from an online survey of 324 qualified respondents were analyzed using the structural equation model. The results of the survey showed that first, perceived economic benefits and perceived usefulness has a positively effect on consumers' positive emotions. Second, perceived privacy risks have a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For example, Kalinic et al ( 2019b ) have shown that the opinion of the social environment on peer-to-peer mobile payment systems influences the decision of potential users to use one means of payment or another. Second, recent studies have shown that the S-O-R model is suitable for addressing consumer behaviour in payment systems (Kim and Rha 2016 ; Chen et al 2019 ; Yuan et al 2020 ). For example, Chen et al ( 2019 ) found that utilitarian value, hedonic value and salesperson behaviour towards mobile payments (S) influence user satisfaction (O), which in turn determines the intention to use mobile payments (R).…”
Section: Theoretical Framework Developmentmentioning
confidence: 99%
“…For example, Kalinic et al ( 2019b ) have shown that the opinion of the social environment on peer-to-peer mobile payment systems influences the decision of potential users to use one means of payment or another. Second, recent studies have shown that the S-O-R model is suitable for addressing consumer behaviour in payment systems (Kim and Rha 2016 ; Chen et al 2019 ; Yuan et al 2020 ). For example, Chen et al ( 2019 ) found that utilitarian value, hedonic value and salesperson behaviour towards mobile payments (S) influence user satisfaction (O), which in turn determines the intention to use mobile payments (R).…”
Section: Theoretical Framework Developmentmentioning
confidence: 99%
“…Moreover, the S-R model or its extensions has been applied in different industries by several studies. These include the mobile telecom industry (Kim & Rha, 2016;Alsaggaf & Althonayan, 2018;Cheng, Chung and Tsai, 2019), retail industry (Chang, Eckman & Yan, 2011;Graa & Dani-elkemir, 2012;Goi, Kalidas & Zeeshan, 2014) and restaurant industry (Segson & Tan, 2018). Others include the online shopping industry (Peng & Kim, 2014) and flea market industry (de Villiers et al, 2017).…”
Section: Review Of Related Literature Theoretical Framework: Stimulus...mentioning
confidence: 99%
“…Moreover, the S-R model or its extensions has been applied in different industries by several studies. These include the mobile telecom industry (Kim &Rha, 2016;Alsaggaf&Althonayan, 2018;Cheng, Chung and Tsai, 2019), retail industry (Chang, Eckman& Yan, 2011;Graa&Danielkemir, 2012;Goi, Kalidas&Zeeshan, 2014) and restaurant industry (Segson& Tan, 2018). Others include the online shopping industry (Peng& Kim, 2014) and flea market industry (de Villiers et al, 2017).…”
Section: Scope Of the Studymentioning
confidence: 99%